Unravelling neomorphism: recrystallization pathways in Proterozoic microfossiliferous chert - Gauvey, Kaitlyn; Kah, Linda C. (Frontiers in Earth Science, 2025)
Early diagenetic chert serves as a critical archive of life on Earth, yet the mechanisms of chert formation and diagenesis remain uncertain. The present research deciphers chert formation and recrystallization through petrographic observations of Proterozoic microfossiliferous chert and explores its relationship to microfossil preservation. Petrographic analyses reveal that the primary chert fabric consists of a network of spherules that consist of chalcedony fibers that radiate outward from a central nucleation point. Original spherules then undergo neomorphic recrystallization that results in systematic grain coarsening and a range of distinctive textures. Subsequent recrystallization can largely erase evidence of primary spherules, but often maintains distinct internal domains within crystals that exhibit sweeping extinction consistent with initial spherulitic growth. We attribute the range of neomorphic features described here to a combination of 1) growth of initial chalcedony spherules within a silica gel that permeates the primary substrate, 2) the degree of alignment of the chalcedony fibers within and between adjacent spherules, 3) the behavior of the amorphous silica component within and external to chalcedony spherules during early neomorphic recrystallization, and 4) coalescence of adjacent grains with similar lattice orientation. Notably, in nearly all cases, remarkable fidelity is maintained in the preservation of microfossil morphology and primary sedimentary fabrics. These observations lead us to a refined model for microfossil silicification and emphasizes both the complex role of neomorphism in chert formation and the low levels of water-rock interaction required for the neomorphic process.